2002
DOI: 10.1046/j.1523-1755.2002.00142.x
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral blood flow and vasodilatory capacity in anemia secondary to chronic renal failure

Abstract: The present study revealed the existence of a reduced cerebral vasodilatory capacity in anemic patients with CRF, suggesting that chronic hypoxic brain damage might play a role in the impaired cerebrovascular response to CO2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

15
75
4

Year Published

2003
2003
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(94 citation statements)
references
References 18 publications
15
75
4
Order By: Relevance
“…Similarly, Vorstrup et al (1992) reported that CBF in their hemodialysis patients was high owing to anemia, but when corrected to control Hct values was significantly reduced, suggesting metabolic reductions. Reduced CMRO 2 and slightly elevated OEF, with anemiaassociated hyperemia, in interdialytic day were also found by Kuwabara et al (2002). These previous results are consistent with our finding of CBF reductions by 19% (in interdialytic ASL-MRI studies) and 40% (ICA BF at the start of dialysis) in non-anemic hemodialysis patients.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, Vorstrup et al (1992) reported that CBF in their hemodialysis patients was high owing to anemia, but when corrected to control Hct values was significantly reduced, suggesting metabolic reductions. Reduced CMRO 2 and slightly elevated OEF, with anemiaassociated hyperemia, in interdialytic day were also found by Kuwabara et al (2002). These previous results are consistent with our finding of CBF reductions by 19% (in interdialytic ASL-MRI studies) and 40% (ICA BF at the start of dialysis) in non-anemic hemodialysis patients.…”
Section: Discussionsupporting
confidence: 92%
“…9 Different hemodynamic disturbances have been reported in patients with CKD. 10,11 Nevertheless, it is not clear whether impaired kidney function is associated with lower cerebral blood flow in the general population. Therefore, we aimed to investigate the association between different measures of kidney function and cerebral blood flow in a population-based cohort of individuals 45 years old and older.…”
mentioning
confidence: 99%
“…5 Interestingly, an animal study suggested that myogenic constriction of cerebral arteries is impaired in uremic hypertensive rats. 8 In addition, a human study demonstrated that cerebral vasodilatory capacity is decreased in patients with anemia secondary to chronic renal failure, 9 indicating that anemia deserves more attention, although hematologic findings have rarely been described in this syndrome. 3 Considering the frequent occurrence of peridialytic blood pressure changes, 10 it is tempting to speculate that blood pressure changes contribute to failed autoregulation of perforating arteries, resulting in edematous lentiform nucleus lesions in cases of long-term kidney failure, particularly in those with diabetes and anemia.…”
mentioning
confidence: 99%